2021
DOI: 10.3389/fcell.2021.697539
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Attenuates Disturbed Flow-Induced Vascular Dysfunction by Inhibiting Force-Specific Activation of Smad1/5

Abstract: BackgroundPathophysiological vascular remodeling in response to disturbed flow with low and oscillatory shear stress (OSS) plays important roles in atherosclerosis progression. Pomegranate extraction (PE) was reported having anti-atherogenic effects. However, whether it can exert a beneficial effect against disturbed flow-induced pathophysiological vascular remodeling to inhibit atherosclerosis remains unclear. The present study aims at investigating the anti-atherogenic effects of pomegranate peel polyphenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
5
0
2
Order By: Relevance
“…Na pesquisa realizada por Anwaier et al (2021) foi observado que a ativação do receptor smads constitui-se também um importante sítio de ação em que é possível intervir por meio da hemodinâmica e assim tratar distúrbios vasculares decorrentes do fluxo instável. Além disso foi observado como o extrato da casca da romã, rica em polifenóis, especialmente punicalagina desempenha sua função antiaterogênica por intermédio da diminuição do LDL e consequentemente das células espumosas.…”
Section: Resultsunclassified
“…Na pesquisa realizada por Anwaier et al (2021) foi observado que a ativação do receptor smads constitui-se também um importante sítio de ação em que é possível intervir por meio da hemodinâmica e assim tratar distúrbios vasculares decorrentes do fluxo instável. Além disso foi observado como o extrato da casca da romã, rica em polifenóis, especialmente punicalagina desempenha sua função antiaterogênica por intermédio da diminuição do LDL e consequentemente das células espumosas.…”
Section: Resultsunclassified
“…Evidence shows the potential interaction of ALB in the blood with Aβ. As such, to improve AD and aging brain lesions, Pun may influence Aβ in the circulatory system by activating ALB . A cohort study demonstrated that brain AKT phosphorylation (pT 308 AKT1/total AKT1) is a key node of growth factors signal transduction, for example, insulin, which is associated with AD neuropathology and cognitive dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…As such, to improve AD and aging brain lesions, Pun may influence Aβ in the circulatory system by activating ALB. 7 A cohort study demonstrated that brain AKT phosphorylation (pT 308 AKT1/total AKT1) is a key node of growth factors signal transduction, for example, insulin, which is associated with AD neuropathology and cognitive dysfunction. 8 More evidence has shown a role for the tyrosine phosphotransferase Fyn of SRC family nonreceptor kinases in the pathophysiological changes of AD.…”
Section: Discussionmentioning
confidence: 99%
“…During this change, growth factors, vasoactive substances, and hemodynamics play important roles [77]. Punicalagin, a natural small molecule, prevents vascular remodeling by inhibiting the specific activation of Smad1/5 in human ECs [59].…”
Section: Vascular Remodelingmentioning
confidence: 99%